Anxiety a very short introduction - Freeman, Daniel, 1971-; Freeman, Jason (Jason Ryan) (Oxford : Oxford University Press, 2012)
Are we born with our fears or do we learn them? Why do our fears persist? What purpose does anxiety serve? In this 'Very Short Introduction' we discover what anxiety is, what causes it, and how it can be treated.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anxiety; Anxiety disorders -- Treatment